2008
DOI: 10.1590/s0074-02762008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization due to norovirus and genotypes of rotavirus in pediatric patients, state of Espírito Santo

Abstract: Viruses are the leading cause for hospitalization due to gastroenteritis worldwide. Group A rotaviruses (RV) are the most prevalent and are assorted in glycoproteins (G)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
4
20
3
3
Order By: Relevance
“…NoV prevalence (7.9%) was similar to that observed for RV-A (7.9%) (3) and highlights the importance of these viruses in children's communities, especially because an increasing number of studies have observed the prevalence and clinical impact of NoVs in the same range as observed for RV-A (13,28,29).…”
Section: Discussionsupporting
confidence: 73%
“…NoV prevalence (7.9%) was similar to that observed for RV-A (7.9%) (3) and highlights the importance of these viruses in children's communities, especially because an increasing number of studies have observed the prevalence and clinical impact of NoVs in the same range as observed for RV-A (13,28,29).…”
Section: Discussionsupporting
confidence: 73%
“…Because NoV diagnosis is not performed routinely in the country, data concerning NoV epidemiology result from studies carried out only by research laboratories that have separately assessed the rate of infection and genetic diversity of NoV in communities, outpatients or children admitted to hospital [Parks et al, 1999;Gallimore et al, 2004;Castilho et al, 2006;Soares et al, 2007;Victoria et al, 2007;Campos et al, 2008;Ferreira et al, 2008;Ribeiro et al, 2008;Xavier et al, 2009]. This 4-year long NoV surveillance study enrolled rotavirus-negative outpatients and inpatients, and assessed the rate, clinical manifestations and molecular epidemiology of NoV in the State of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 99%
“…11 Over the last 3 years a number of studies have investigated the prevalence of NoV infection in hospitalised children. 5 A wide range of prevalences (6-48%) were reported with a median of 14%, 5 and in some studies NoV-associated gastroenteritis was almost as common as RV infections [12][13][14] indicating that NoVs may be clinically more relevant than previously thought. NoV-associated gastroenteritis outbreaks were first reported in South Africa (SA) in 1993.…”
Section: Introductionmentioning
confidence: 98%